Applying Sharing Session in Encouraging and Motivating Students in Language Learning Class - Marchellina Wijaya (Journal of English Education, 2021)
The purpose of this paper is to analyze the importance of sharing sessions in encouraging and motivating students in the language learning class. Not all of the students are active in the class, some students are passive in the class because of some factors. When the teacher asks the question, students preferably keep silent in the class. They are becoming passive participants in the class because they do not know the topic and feel unconfident to speak in front of others.  They are becoming afraid to speak because they do not feel comfortable in the class situation and condition.  They do not have good socialization in the class like they do not respond well and give feedback in the class. For this problem, this paper attempts to analyze how to apply the sharing session steps in language learning class and what are the benefits of applying them.  The teacher can give motivation like intrinsic or extrinsic motivation in a sharing session class which also can encourage students in language learning class. This paper applies qualitative research analysis and also a descriptive method to describe the finding. Two steps can be used to apply sharing sessions in encouraging and motivating students in the language learning class. The first step is to choose the learning materials that are appropriate for the learners, and the second step is to create good classroom management. This paper finally underlines that the use of applied learning materials that are appropriate with the learners and create good classroom management can improve students’ confidence, and it makes them be the independent learners in the classroom.